COMPARATIVE PHARMACOGNOSTIC, PHYSICOCHEMICAL AND PHYTOCHEMICAL STUDIES OF DIFFERENT SAMPLES OF PLUMBAGO ZEYLANICA L. ROOTS (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
The objective of the present study is to evaluate the quality of the marketed and self collected samples of Plumbago zeylanica L. roots on the standardization parameters. This study is planned mainly to confirm changes with quality of drug. Now a day’s more demand of herbal drugs for disease treatment, lack of knowledge of proper methodology and availability are promoting the practices of adulteration and substitution. Thus, the standardization of the plant crude drugs is necessary to maintain their therapeutic efficacy. Comparative studies were carried out to evaluate the standards of P. zeylanica L. with emphasis on organoleptic evaluation, physicochemical and phytochemical analysis. Samples were procured from local market and self collected to determine the qualitative and quantitative variations. The result indicates that self collected sample showed significant results with comparison to marketed sample.